The Max Born Symmetry Topples the Many-Worlds Theory (JOURNAL OF ADVANCES IN PHYSICS, 2022)
All “interpretations” of Quantum Mechanics (QM) are predicated on the assumption that quantum mathematics is correct. We disagree. The Born rule implies that nature may have a hidden symmetry: |+ψ|2 = |–ψ|2 = probability. If nature uses –ψ then physicists would not recognize that their math is 100% wrong. This hypothesis could explain the mystery that quantum math appears to be the most accurate and productive mathematics humans ever possessed, the source of our high-tech economy, yet scientists cannot agree on what the quantum world is like: does it exist, are there infinitely many worlds, etc. If we change our wave-function from +ψ to –ψ, that will mean that quantum particles follow zero-energy “Elementary Waves” backwards. This symmetry does not conform to Noether’s Theorem because it does not involve physical space, rather an error in the human imagination. Wave-function collapse no longer occurs when a quantum particle is observed. It occurs when a free particle is emitted: when the particle selects which in-coming Elementary Wave to follow backwards. This undermines the foundations of the many-worlds theory. A superposition of states collapses as a particle is emitted, becoming only one state, located in only one world, not many.Type (Method/Approach): No one previously recognized the Born rule could hide a “Born Symmetry”: |+ψ|2 ≡ |–ψ|2. If so, it would be so immense, pervasive, insidious, and invisible that it could explain all quantum “weirdness” even though quantum math is the most accurate and productive science ever.